Constructing visual images in creative sign language in solo and collaborative performance: Space and embodiment. Issue 3 (3rd July 2017) - Sutton-Spence, Rachel
ABSTRACT: This article considers ways in which signing poets use space to produce visual images, creating aesthetic and metaphorical effects using the options available to sign languages and their bodies, whether in a solo performance or jointly constructed as duets or living tableaus. Close reading of sign language poetry shows poets use their bodies to demonstrate poetic images directly, by embodying the referent so they 'become' it, or by showing it through a transfer onto different parts of the body. Even richer images with additional metaphorical meaning arise when poets perform with others, especially to convey concepts of contrast or unity. The article draws primarily upon poetic performances in South African Sign Language (SASL) at Signing Hands Across the Water 2, an international sign poetry festival held in Johannesburg in 2014. It also considers works in Brazilian Sign Language (Libras) and British Sign Language (BSL) – two languages whose rich poetic activity has not yet received much research interest. Analysis of this creative work offers ways for poets working in any sign language to develop their creations. Additionally, such an analysis informs the wider artistic and literary world about possibilities for creating visual linguistic art forms.